A review of the existing legislation in regulating the dental profession and practices in Malaysia / Musfirah Musa - Musa, Musfirah (2016)
This study involves the legal issue surrounding the dental profession in Malaysia. Currently there are multiple foreseen and unforeseen problems that arise from the state of the existing laws and its procedures. Regulation of the dental profession and its services is conducted by two different bodies which are the Malaysian Dental Council and Enforcement Unit. Regulation by two different bodies creates conflict of interest between them. For the issue that exist to be resolved, a more stringent rule needs to be regulated and a clear procedure be established amongst those agencies involved in the dental profession. Hopefully this will ensure the safety of the public and integrity of the profession itself. The objective of this study is to highlight the lacuna in the Dental Act 1971 and Private Healthcare Facilities and Services Act 1998 with the ultimate aim of formulating a proposal to rectify the weaknesses. Explicitly the Acts are referred throughout the research, with certain emphasis on the enforcement powers and a limited comparative study on the dental related laws of United Kingdom. A qualitative approach was adopted with concentration on doctrinal research combined with fieldwork. Due to some limitation and constraints, the doctrinal research mainly concentrated in library based research that covered various literatures and related Acts. Semi structured interviews had been carried out with selected individuals having the necessary experience and competent authority. Conclusively the result of the research corresponds to the objective and answered most of the queries and offered a solid proposal for rectifications.